ANALISA JATUH TEGANGAN PADA JARINGAN TEGANGAN RENDAH Di PT.PLN (Persero) ULP Lembata - Ekawati, Elfira Dyah; Lamataro, Fadly; Suheta, Titiek; Wicaksono, M. Rizki; Ikhwanunnadzir, Yani (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2023)
We need good service quality in the electric power operating system, such as providing a good voltage value to customers and no voltage drop disturbance. This study determined the relationship between load balancing and voltage drop. It involved literature, observation, and interview methods. The analysis results at the LB.06 substation obtained the load value before load balancing on holidays in the morning and evening by 37.95% and 42.13%, while effective days gained 41.99% and 44.15%. The voltage drops after load balancing in holiday achieved R-phase 2.15%; 3.41%; S- phase 2.58%; 1.74%; and T-phase 3.56%; 5.98%. Meanwhile, effective days achieved R-phase 3.43%;4.27%, S-phase 1.73%;0.43%, and T-phase 2.60%;1.28%. In conclusion, load balancing was effective enough to reduce load and voltage drop values.